2022
DOI: 10.1021/jacs.2c08531
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic and Aromatic C–H Bond Oxidation by High-Valent Manganese(IV)-Hydroxo Species

Abstract: The strong C−H bond activation of hydrocarbons is a difficult reaction in environmental and biological chemistry. Herein, a high-valent manganese(IV)-hydroxo complex, [Mn IV (CHDAP-O)(OH)] 2+ (2), was synthesized and characterized by various physicochemical measurements, such as ultraviolet−visible (UV−vis), electrospray ionization-mass spectrometry (ESI-MS), electron paramagnetic resonance (EPR), and helium-tagging infrared photodissociation (IRPD) methods. The one-electron reduction potential (E red ) of 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 91 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…To define the mechanism of the reaction of haloacetonitrile with the ionic or neutral Cu(I) species further, we performed density functional theory (DFT) calculations with the PBE0-D3(BJ) functional. On the basis of previous proposals for the mechanism of copper-mediated cross-coupling reactions (18)(19)(20)(21)(22) and the experimental results reported in this work, we proposed five different pathways that could account for the oxidative addition of haloacetonitrile to ionic and neutral Cu(I) complexes (Fig. 4).…”
Section: Activation Parametersmentioning
confidence: 63%
See 1 more Smart Citation
“…To define the mechanism of the reaction of haloacetonitrile with the ionic or neutral Cu(I) species further, we performed density functional theory (DFT) calculations with the PBE0-D3(BJ) functional. On the basis of previous proposals for the mechanism of copper-mediated cross-coupling reactions (18)(19)(20)(21)(22) and the experimental results reported in this work, we proposed five different pathways that could account for the oxidative addition of haloacetonitrile to ionic and neutral Cu(I) complexes (Fig. 4).…”
Section: Activation Parametersmentioning
confidence: 63%
“…Previously, two distinct cycles were proposed for copper-catalyzed cross-coupling reactions of alkyl electrophiles. One cycle comprises a two-electron Cu(I)/Cu(III) manifold, and one comprises a stepwise Cu(I)/Cu(II) manifold involving initial single-electron transfer (SET) between the Cu(I) center and the alkyl electrophile to generate a Cu(II) intermediate and an alkyl radical, followed by transfer of the functional group from the resulting Cu(II) species to the alkyl radical (18)(19)(20)(21)(22) (Fig. 1A).…”
mentioning
confidence: 99%
“…Under the same conditions, the initial oxidation rate of 3,5-DTBC by Cu-Cl-bpyc was the fastest. For a direct comparison, the aromatic C−H bond oxidation of anthracene to anthracene-9,10-dione was chosen as the model reaction, 68 as the aromatic oxidation does not occur via a hydrogen atom abstraction, but involves an initial electrophilic attack on the πsystem of the aromatic ring to produce a radical or cationic σcomplex. As shown in Figure 5c, our catalytic results showed that the three catalysts oxidized anthracene to anthracene-9,10dione with good yields, but Cu-Cl-bpyc gave the highest yield.…”
Section: •−mentioning
confidence: 99%
“…As demonstrated previously, an effective way to detect and study reactive metal complexes is to generate them in a flow reactor with a direct connection to a mass spectrometer with an electrospray ionization interphase (ESI-MS). [39][40][41] Reaction of (TPA)Fe(OTf) 2 with phenyl dioxazolone (A) in a flow reactor (Figure 1a) leads to the detection of a dominant ESI-MS signal with a mass corresponding to the iron-acyl-nitrenoid complex with additional acetonitrile ligand ([(TPA)Fe(NCOPh)(MeCN)] 2 + (2), m/z 253.07, Figure 1b, top). In addition, we detected less abundant signals of the triflato analog ([(TPA)Fe(NCOPh)(OTf)] + , m/z 614.07, Figure S2A) and the complex without the additional ligand ([(TPA)Fe(NCOPh)] 2 + , m/z 232.56, Figure 1b, top).…”
Section: Resultsmentioning
confidence: 99%